Aflasafe MWMZ01 and Aflasafe MZ02 for Mozambique - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In February 2019, two Aflasafe products were registered in Mozambique. By the end of 2019, IITA was still in the process of mobilising potential investors for commercial deployment.